Effect of SiNx gate insulator thickness on electrical properties of SiNx/In0.17Al0.83N/AlN/GaN MIS–HEMTs. (April 2015) - Downey, B.P.; Meyer, D.J.; Katzer, D.S.; Marron, T.M.; Pan, M.; Gao, X.
Highlights: SiN x was deposited in an MBE chamber on InAlN/AlN/GaN HEMTs. HEMTs had ultra-thin (sub-critical) InAlN/AlN (2.3 nm/1 nm) barrier. Negative shift in threshold voltage measured with increasing SiN x thickness. Positive charge at the SiN x /InAlN interface was extracted from threshold shift. Thin SiN x can induce low resistance channel in sub-critical barrier devices. Abstract: The effect of SiN x thickness on device characteristics such as threshold voltage, carrier density, and carrier mobility have been determined for a metal–organic chemical-vapor-deposition grown In0.17 Al0.83 N/AlN/GaN structure with an ultra-thin In0.17 Al0.83 N/AlN (2.3/1 nm) barrier layer. The SiN x gate dielectric was deposited ex situ in an RF plasma assisted molecular beam epitaxy system. The threshold voltage shifts negatively and the carrier density increases as the SiN x thickness is increased from 1 to 6 nm due to the presence of a positive charge at the SiN x /In0.17 Al0.83 N interface. An interfacial charge of +3.84 × 10 13  cm −2 was extracted through the dependence of threshold voltage on insulator thickness. While remote charge scattering from the interfacial charge is shown to limit the carrier mobility, values as high as 1550 cm 2 /V s were achieved. Low gate and off-state drain leakage currents of less than 500 nA/mm, a drain current ON/OFF ratio of approximately 10 7, and a normalized three terminal breakdown voltage of approximately 60–80 V/μm gate–drain spacing were achieved on these ultra-thin In0.17 Al0.83 N/AlN barrier devices by implementing a thin SiN x gate insulator. The ability to maintain a short gate-to-channel distance while utilizing a gate insulator for reduced leakage current and improved breakdown can provide a pathway for higher power millimeter-wavelength amplifier performance.